Audiencias Activas en el uso del Facebook y obtención de gratificaciones - Vidaurre Güiza, Carmen (2014)
The essay is based on the incorporation of Facebook in the interaction processes of users, virtual space where private matters become public. A radical transformation of the function of the audience is assumed. The nature of this study is structuralist based on the Uses and Gratifications theory which can be achieved with media contents. From the communicator’s point of view, discourse significance is analyzed. Also the characteristics of virtual discourse is presented in the case of a person with 1567 “friends” on his Facebook account, whosoon after writing a question obtains 123 “Likes” and 92 comments expressing feelings and opinions in favor and against.